THE INFLUENCE OF PRODUCT INNOVATION AND PRODUCT ATTRIBUTES ON EVERBRIGHT SALES LEVELS BINJAI BRANCH - Mila Asmawiani Okta; Galeh Sari (PT. MITRA ANGKASA INFORMATIKA, 2024)
This research was conducted at PT Everbright Binjai Branch. The aim of this research was to determine and analyze the influence of Product Innovation and Product Attributes on the Sales Level of PT Everbright Binjai Branch. The population is 126 customers, while the sample in this research is: 96 customers. The sampling technique used is simple random sampling. Data collection techniques are by distributing questionnaires, interviews and documentation studies. Data analysis uses multiple linear regression analysis. The conclusion of the research is that simultaneously Product Innovation and Product Attributes have a positive and significant effect on the Sales Level of PT Everbright Binjai Branch. Partially, Product Innovation has a positive and significant effect on the Sales Level of PT Everbright Binjai Branch. Partially, Product Attributes have a positive and significant effect on the Sales Level of PT Everbright Binjai Branch. The coefficient of determination seen from the Adjusted R Square value is: 0.435, meaning that product innovation and product attributes can explain the sales level by 43.5% and the remaining 56.5% is influenced by other variables outside of this research such as: service quality, sales promotion. , customer satisfaction and so on. Keywords: Product Innovation, Product Attributes, Sales Level Keywords